Daily evolution in dust and black carbon content, snow grain size, and snow albedo during snowmelt, Rocky Mountains, Colorado - S. McKENZIE SKILES; THOMAS PAINTER (Journal of Glaciology, 2017)
Light absorbing impurities (LAI) initiate powerful snow albedo feedbacks, yet due to a scarcity of observations and measurements, LAI radiative forcing is often neglected or poorly constrained in climate and hydrological models. To support physically-based modeling of LAI processes, daily measurements of dust and black carbon (BC) stratigraphy, optical grain size, snow density and spectral albedo were collected over the 2013 ablation season in the Rocky Mountains, CO. Surface impurity concentrations exhibited a wide range of values (0.02–6.0 mg g−1 pptw) with 98% of mass being deposited by three episodic dust events in April. Even minor dust loading initiated albedo decline, and the negative relationship between dust concentrations and albedo was log-linear. As melt progressed, individual dust layers coalesced and emerged at the snow surface, with minimal mass loss to meltwater scavenging. The observations show that the convergence of dust layers at the surface reduced albedo to 0.3 and snow depth declined ~50% faster than other years with similar depth but less dust. The rapid melt led to an unexpected reduction in both grain size and density in uppermost surface layers. BC concentrations co-varied with dust concentrations but were several orders of magnitude lower (<1–20 ppb).